Splenic sea-blue (ceroid) histiocytosis due to hypertriglyceridemia: Report of a case and review of literature - Kacy A. Krehbiel; Robert H. Glew; Sheila Modi; Mohammad A. Vasef (Elsevier, 2017)
Sea-blue histiocytosis is a rare condition that can be often identified in bone marrow, spleen, liver as well as other organs. It can be frequently detected in bone marrow of patients with myeloproliferative neoplasms as well as non-neoplastic conditions such as idiopathic thrombocytopenic purpura. In this study, we report pathologic findings in a case of sea-blue histiocytosis of spleen in a patient who presented with abdominal pain and elevated triglycerides. The sea-blue histiocytosis was identified as an unexpected finding in this previously healthy individual. This case illustrates the necessity of good communication between clinicians and pathologists for the identification and treatment of the underlying lipid disorders. The prior cases of sea-blue histiocytosis reported in English literature are reviewed and the differential diagnoses are discussed. Keywords: Sea-blue histiocytes, Splenomegaly, Hypertriglyceridemia